Study on interactive effect of heat treatment and enzymatic activities in mature coconut water upon storage - Yee Syuan, Yew (2025)
Mature coconut water (MCW), though nutritionally valuable, is often discarded during coconut milk production. Factors such as heat treatment, sugar addition and enzymatic activity could lead to browning of MCW during processing and storage. Phenolic compounds in coconut water serve as substrate for enzymatic browning. Chitin, a renewable biopolymer has been widely applied in wastewater treatment and white wine production to remove phenolic compounds. However, research on its application in coconut water is limited. This study examined the effects of heat treatments (water bath, W; pressure cooking, P) and their combinations with chitin (CW, CP) on enzymatic browning in MCW. Changes in total phenolic content (TPC), browning index (BI), polyphenol oxidase (PPO) activity and peroxidase (POD) activity were monitored over 12 days. POD were absent in all samples, whereas PPO activity was highest in untreated MCW (control) and progressively decreased in W (64.00 ± 0.00 U/mL), CW (40.00 ± 0.00 U/mL) and was undetectable in P and CP (0.00 ± 0.00 U/mL) by Day 12. W and CW did not inhibit the browning (a progressive increase of BI from Day 0 to Day 12 storage). In contrast, P and CP treatments significantly suppressed browning in MCW, with no significant changes in BI between Day 0 and Day 12. These findings suggest that pressure-cooking is more effective in controlling browning, with no notable difference between P and CP. Chitin application in MCW requires further study, as its effectiveness appears highly dependent on the surrounding chemical environment. Overall, the combination of chitin and heat treatment showed similar effects to heat treatment alone. Despite these challenges, MCW retains potential for commercialization as a sports drink alternative due to its beneficial properties, although further research is needed to develop a product that is both appealing and nutritious.